Cold-Pressed Nigella Sativa Oil Standardized to 3% Thymoquinone Potentiates Omega-3 Protection against Obesity-Induced Oxidative Stress, Inflammation, and Markers of Insulin Resistance Accompanied with Conversion of White to Beige Fat in Mice - Hsin Hsueh Shen; Stephen J. Peterson; Lars Bellner; Abu Choudhary; Lior Levy; Leah Gancz; Ariel Sasson; Joseph Trainer; Rita Rezzani; Abraham Resnick; David E. Stec; Nader G. Abraham (MDPI AG, 2020)
Excessive lipid accumulation in white adipose tissue (WAT) results in adipocyte hypertrophy and chronic low-grade inflammation, which is the major cause of obesity-associated insulin resistance and consequent metabolic disease. The development of beige adipocytes in WAT (browning of WAT) increases energy expenditure and has been considered as a novel strategy to counteract obesity. Thymoquinone (TQ) is the main bioactive quinone derived from the plant Nigella Sativa and has antioxidative and anti-inflammatory capacities. Fish oil omega 3 (ω3) enhances both insulin sensitivity and glucose homeostasis in obesity, but the involved mechanisms remain unclear. The aim of this study is to explore the effects of TQ and ω3 PUFAs (polyunsaturated fatty acids) on obesity-associated inflammation, markers of insulin resistance, and the metabolic effects of adipose tissue browning. 3T3-L1 cells were cultured to investigate the effects of TQ and ω3 on the browning of WAT. C57BL/6J mice were fed a high-fat diet (HFD), supplemented with 0.75% TQ, and 2% ω3 in combination for eight weeks. In 3T3-L1 cells, TQ and ω3 reduced lipid droplet size and increased hallmarks of beige adipocytes such as uncoupling protein-1 (UCP1), PR domain containing 16 (PRDM16), fibroblast growth factor 21 (FGF21), Sirtuin 1 (Sirt1), Mitofusion 2 (Mfn2), and heme oxygenase 1 (HO-1) protein expression, as well as increased the phosphorylation of Protein Kinase B (AKT) and insulin receptors. In the adipose tissue of HFD mice, TQ and ω3 treatment attenuated levels of inflammatory adipokines, Nephroblastoma Overexpressed (NOV/CCN3) and Twist related protein 2 (TWIST2), and diminished adipocyte hypoxia by decreasing HIF1α expression and hallmarks of beige adipocytes such as UCP1, PRDM16, FGF21, and mitochondrial biogenesis markers Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α), Sirt1, and Mfn2. Increased 5' adenosine monophosphate-activated protein kinase (AMPK) and acetyl-CoA carboxylase (ACC) phosphorylation and HO-1 expression were observed in adipose with TQ and ω3 treatment, which led to increased pAKT and pIRS1 Ser307 expression. In addition to the adipose, TQ and ω3 also increased inflammation and markers of insulin sensitivity in the liver, as demonstrated by increased phosphorylated insulin receptor (pIR tyr972), insulin receptor beta (IRβ), UCP1, and pIRS1 Ser307 and reduced NOV/CCN3 expression. Our data demonstrate the enhanced browning of WAT from TQ treatment in combination with ω3, which may play an important role in decreasing obesity-associated insulin resistance and in reducing the chronic inflammatory state of obesity.